Development of 21st Century Skills via a Social Service Program at the Tertiary Education Level in Indonesia - Kiettikunwong, Narong; Narot, Pennee; Istiq’faroh, Nurul; Setiawan, Ricky; Deeod, Pongmanut (Journal of Ecohumanism, 2025)
This case study examines the development of 21st century skills through Indonesia’s Social Learning Service Program (KKN) and investigates factors supporting its implementation at UNTAG, Surabaya. Using a qualitative approach, data were collected through interviews with key informants including university administrators, lecturers, students, and community members, along with field observations and document analysis. The findings reveal that the KKN program, established in 1951, has evolved through four modifications to become a mandatory curriculum component in Indonesian universities. The program’s success is attributed to effective leadership, stakeholder participation, strong teamwork, knowledge transfer, and autonomous program management. The learning process follows a project-based approach with four phases: Preparation, Action, After Action, and Evaluation, allowing students to apply theoretical knowledge in real-world situations. This study demonstrates how social service programs can effectively develop essential 21st century competencies in higher education students while contributing to community development. The findings provide valuable insights for higher education institutions seeking to integrate service learning with skills development for the 21st century workforce.